Exploring the impacts of microclimatic temperature on occupancy of the Apollo butterfly (Parnassius apollo) - Laaksonlaita, Jussi (My University, 2023)
Climate driven environmental conditions and division of resources have a key role in determining the distribution of ecosystems and organisms. Ongoing anthropogenic climate change has already enabled some species to expand their distribution or limits the range of others. Species living in northern latitudes and mountainous habitats are especially vulnerable to the effects of climate change and it’s challenging their capability to adapt. Recent studies have shown that microclimates may buffer the effects of climate change by providing thermal niches, where the species are able to persist. Butterflies, such as the study species Parnassius apollo, is one of the groups most affected by the temperature rise. Their habitat selection, life cycle, and survival are often dependent on thermal conditions. Furthermore, both ambient temperature and microclimatic variation can affect ovipositing behavior of butterflies. The decline of P. apollo has been rapid in recent decades, and the reasons behind it are still largely unknown. In my study, I investigate if the species occupancy is related to temperature differences of the available habitat patches. Furthermore, I examine if the larvae distribution within habitat patch is impacted by the small-scale thermal variation. I deployed temperature loggers on 35 rocky outcrops within the known distribution area of P. apollo in Parainen, SW Finland. Detailed census, including survey of larvae occupancy and abundance, and host plant (H. telephium) count, was carried out on all patches in spring 2020. In addition to above, total of 18 temperature loggers (6 on each) were deployed on three selected habitat patches to investigate the small-scale thermal variation of the occupied patches. I found out that the habitat patches occupied by P. apollo are warmer than the unoccupied ones, both when comparing mean and minimum temperatures of larvae period (29.4.-15.6.) and wing-time (1.7.-15.8.). No difference in maximum temperatures was found. Based on my results, the spring mean and summer minimum temperatures are the temperature variables with the biggest effect on occupancy and larvae abundance. Moreover, there was no significant difference in the number or density of host plants between occupied or unoccupied patches. However, the occupied patches were larger. When inspecting the small-scale thermal variation of occupied patches, the maximum temperatures were higher in cells with larvae and host plant than in cells with just host plant growing only on one patch. Yet, also when inspecting other locations and variables, the larvae were mostly found from warmer cells (p > 0,05). Even though, the earlier studies suggest that the host plant abundance is the major factor determining the occupancy of P. apollo, my study shows that microclimatic temperature variation may impact the occupancy and larvae abundance. Further studies are needed to investigate the role of microclimatic conditions on P. apollo occupancy and distribution. Furthermore, I suggest that habitat heterogeneity should be considered when implementing habitat restoration measures, in order to preserve thermal variation on the habitat patches.
Keywords: microclimate, Apollo, Parnassius, occupancy, temperature, butterfly, endangered